A word stemming algorithm for Hausa language - Muazzam, Bashir; Azilawati, Rozaimee; Wan Malini, Wan Isa (2015)
Hausa, a highly inflected language, needs a worthy stemming approach for efficient information retrieval (IR). However, there is a limited or unavailable study to stemming in the language. Stemming refers to the systematic way of reducing a word to its base or root form. It is a crucial aspect in the field of natural language processing (NLP) such as text summarization and machine translation. As such, this study inspirationally presents an automatic word stemming system for Hausa language with a view to contributing to the field of electronic text processing, as well as NLP, in general. The proposed method is a modification of Porter’s algorithm to fit Hausa morphological rules. The system has an accuracy of 73.8% for implementation with 2573 words extracted from four different articles from Hausa Leadership newspaper. If immensely improved over time (employing more exceptional cases in future work), it would inspire the development of more tools for the language. Hence, the language would rapidly adopt the advancement in technology.